PRIORITY SCENARIOS OF THE MANAGER'S BEHAVIOUR IN THE ORGANIZATIONAL CONFLICT ON THE EXAMPLE OF THE JSC «RAMENSKOYE INSTRUMENT-MAKING PLANT» - O. Fomicheva (Publishing House of the State University of Management, 2018)
The organizational conflict from the position of participation of the manager has considered. He is particularly more responsible for the optimal use of resources: their improvement and multiplication. The article makes an analysis of 3 positions, in which the manager can take part: participant, mediator and as an «example of behaviouor». The necessity of developing a training program for managers has justified. Recommendations for the manager, for each of the 3 roles have offered. A General action plan has formulated for both the personnel management service and the management. As an example, the organization of Joint-stock company «Ramensky instrument-making plant» has chosen.